1998
DOI: 10.1002/(sici)1096-9136(199804)15:4<339::aid-dia577>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with clinic non-attendance in adults with Type 1 diabetes mellitus

Abstract: In order to examine the causes of non-attendance in a diabetic clinic, a 1-year retrospective casenote review of 259 diabetic patients with no evidence of major complications was undertaken. Frequency of clinic attendance, clinic non-attendance, and glycaemic control (HbA1c) were recorded. In a sub-sample of 82 patients, more detailed demographic data was obtained via questionnaire. During the previous year 39% of patients had failed to attend the clinic on at least one occasion and 10% were recurrent non-atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 7 publications
0
56
2
2
Order By: Relevance
“…In contrast, we did not find an association with age which has been identified in US studies [11,12,38]. In the US and Canada, younger people are more likely to attend diabetes education [12,19] which could be because they are more likely to be employed and therefore have medical insurance whereas in the UK there is no such incentive [38,39]. Those with better glycaemic control, non-smokers, and those with positive health beliefs about their diabetes treatment are more likely to attend suggests that current models of care are not targeting those who may need it the most and similar patterns have been observed in other health settings, such as diabetes clinics [39], cardiac rehabilitation [40], and mammography screening [41].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In contrast, we did not find an association with age which has been identified in US studies [11,12,38]. In the US and Canada, younger people are more likely to attend diabetes education [12,19] which could be because they are more likely to be employed and therefore have medical insurance whereas in the UK there is no such incentive [38,39]. Those with better glycaemic control, non-smokers, and those with positive health beliefs about their diabetes treatment are more likely to attend suggests that current models of care are not targeting those who may need it the most and similar patterns have been observed in other health settings, such as diabetes clinics [39], cardiac rehabilitation [40], and mammography screening [41].…”
Section: Discussioncontrasting
confidence: 83%
“…In the US and Canada, younger people are more likely to attend diabetes education [12,19] which could be because they are more likely to be employed and therefore have medical insurance whereas in the UK there is no such incentive [38,39]. Those with better glycaemic control, non-smokers, and those with positive health beliefs about their diabetes treatment are more likely to attend suggests that current models of care are not targeting those who may need it the most and similar patterns have been observed in other health settings, such as diabetes clinics [39], cardiac rehabilitation [40], and mammography screening [41]. On a positive note we did not find an association between ethnicity and attendance at structured education, found in one US study [12], although we did broadly group participants into ethnic groups and qualitative research has demonstrated that some West Africans might be opposed to group education for fear of stigmatisation [18].…”
Section: Discussionmentioning
confidence: 99%
“…71 It has been reported that alcoholics, intravenous drug users and those who are pregnant have higher non-attendance rates, 75 as well as past and current smokers. 81,82 Patients who are single parents or have children living at home are more likely to be non-attenders. 81 Those with young, large families are also more likely to miss appointments, 76,83 as well as those with a poor family support system.…”
Section: Return-to-theatre Metrics For Orthopaedicsmentioning
confidence: 99%
“…81,82 Patients who are single parents or have children living at home are more likely to be non-attenders. 81 Those with young, large families are also more likely to miss appointments, 76,83 as well as those with a poor family support system. 69 Area-level deprivation scores are often strong predictors of non-attendance.…”
Section: Return-to-theatre Metrics For Orthopaedicsmentioning
confidence: 99%
“…In two studies [13,14] non attenders were more likely to be male. In two other studies [15,16] attendance was not related to gender.…”
Section: Discussionmentioning
confidence: 72%